Rosuvastatin effects on the HDL proteome in hyperlipidemic patients - Vavlukis Ana; Mladenovska Kristina; Davalieva Katarina; Vavlukis Marija; Dimovski Aleksandar (Acta Pharmaceutica)
The advancements in proteomics have provided a better understanding of the functionality of apolipoproteins and lipoprotein-associated proteins, with the HDL lipoprotein fraction being the most studied. The focus of this study was to evaluate the HDL proteome in dyslipidemic subjects without an established cardiovascular disease, as well as to test whether rosuvastatin treatment alters the HDL proteome. Patients with primary hypercholesterolemia or mixed dyslipidemia were assigned to 20 mg/day rosuvastatin and blood samples were drawn at study entry and after 12 weeks of treatment. A label-free LC-MS/MS protein profiling was conducted, coupled with bioinformatics analysis. Sixty-nine HDL proteins were identified, belonging to four main biological function clusters: lipid transport and metabolism; platelet activation, degranulation, and aggregation, wound response and wound healing; immune response; inflammatory and acute phase response. Five HDL proteins showed statistically significant differences in the abundance (Anova ≤ 0.05), before and after rosuvastatin treatment. Platelet factor 4 variant (PF4V1), Pregnancy-specific beta-1-glycoprotein 2 (PSG2), Profilin-1 (PFN1) and Keratin type II cytoskeletal 2 epidermal (KRT2) showed decreased expressions, while Integrin alpha-IIb (ITGA2B) showed an increased expression after treatment with rosuvastatin. The ELISA validation of PFN1 segregated the subjects into responders and non-responders, as PFN1 levels after rosuvastatin were shown to mostly depend on the subjects’ inflammatory phenotype. Findings from this study introduce novel insights into the HDL proteome and statin pleiotropism.